Factors of Acute Diarrhoea among Children of Under Five Years Old in Sabah, Malaysia: A Case-Control Study - Syed Sharizman Syed Abdul Rahim; Shamsul Azhar Shah; Mohammad Saffree Jeffree; Zahir Izuan Azhar; Mohd Rohaizat Hassan; Nazarudin Safian; Narinderjeet Kaur (2020)
Acute diarrhoea is a major public health problem and is the second leading cause of death in children. It has implications in terms of morbidity and mortality especially in the under five years old age group. The purpose of this study was to determine the factors associated with acute diarrhoea among children under 5 years old in Sabah. This was a case-control study involving 584 samples in four districts in Sabah. Analysis with multiple logistic regression discovered the associated factors of acute diarrhoea among under 5 years old were child’s age, single parents aOR5.209 (95%CI 1.09-25.01), Peribumi Sabah mother aOR1.542 (95%CI 1.01-2.34), unemployed mother aOR1.783 (95%CI 1.16-2.75), less than RM2,000 monthly household income aOR1.643 (95%CI 1.08-2.49), no garbage collection aOR1.923 (95%CI 1.24-2.98), adjacent open garbage aOR1.888 (95%CI 1.23-2.91), average rainfall of 151mm or more aOR1.768 (95%CI 1.22-2.56) and less than 1 year of breastfeeding aOR1.685 (95%CI 1.11-2.55). The study has revealed the need to improve the overall level of hygiene and sanitation in the population.